Response to Water Scarcity: Gender Analysis of the Motivation Factors Toward Water Conservation Behavior in the Workplace - Palamuleni, Lobina Gertrude; Plessis, Yvonne du; Bakuwa, Rhoda Cynthia (Frontiers in Water, 2022)
Provision and availability of water continue to be a major socio-economic challenge in many countries. The problem is prevalent particularly in arid and semi-arid regions which are affected by droughts and wide climate variability, combined with high population growth and economic development. Shortages and compromised water availability are causes of concern to food security (agricultural sector), performance of businesses, and economic growth among others. The study adopted a quantitative research approach and was underpinned by a positivist research paradigm. Data were collected from 72 managers at North West University – Mahikeng (NWU-Mahikeng), South Africa using an online self-administered survey questionnaire. This study evaluates the factors related to predictors of water-conservation motivation behaviour at work. The study used the Chi-square statistics (Phi and Cramer’s V tests) to test the relationship between Manager’s gender and motivation predictors of water conservation at work. Findings from the statistical results showed that the Phi and Cramer’s V test gave a P value less than 0.05 (P<0.05), which shows that within the sample of managers, there is significant relationship between Manager’s gender and the motivation to conserve water. These results highlight that gender orientation affects one’s response to water scarcity and motivation for conservation. The variations underscored gender as an important component of sustainable development goals which must be included when implementing policies and programs to promote water conservation consciousness and efficient water use at work.